Taxonomic status of Doydixodon laevifrons (Tschudi, 1846) (Osteichthyes: Kyphosidae) - Pequeño, Germán (2008)
Doydixodon laevifrons is commonly known as baúnco, but in latest papers it has also been cited as Girella laevifrons without any explanation for this change generic. The purpose of this paper is to review the morphological features of diagnostic for the genera Doydixodon Valenciennes, 1846 and Girella Gray, 1835, and their presence or absence in specimens of Doydixodon laevifrons from central Chile. We conclude that Doydixodon laevifrons is synonymous minor (=junior) of Girella laevifrons and it is distributed by the littoral, from the south coast of Peru, until approximately El Tabo (33°27’S, 71°41’W) in Chile. Thus, is the species with southernmost distribution in the genus. A taxonomic revision of the genus Girella Gray, 1835 in the southeastern Pacific, is suggested.